The Role of Service, Product Quality, and Consumer Satisfaction in Driving Repurchase Intention on TikTok Shop - Dwicahyo, Herwanda Rama; Fietroh, Muhammad Nur (Journal of Educational Management Research, 2025)
This study examines the effects of service quality, product quality, and customer satisfaction on repeat purchase intention among TikTok Shop users in Sumbawa Regency. TikTok Shop, as a social commerce platform integrating entertainment with digital transactions, has transformed consumer online shopping behavior. Employing a quantitative approach and multiple linear regression analysis with 100 purposively sampled respondents, the findings indicate that service quality, product quality, and customer satisfaction significantly and positively influence repeat purchase intention both partially and simultaneously. The adjusted R² value of 0.475 suggests that these three independent variables explain 47.5% of the variation in consumers’ repeat purchase intention. These results emphasize the importance of enhancing service and product quality alongside managing customer satisfaction as strategic measures to build customer loyalty and ensure business sustainability, especially for MSMEs in non-metropolitan regions such as Sumbawa Regency. The practical implications of this study can serve as guidelines for developing effective marketing and service strategies on the TikTok Shop platform to improve customer retention. Furthermore, this study contributes empirical insights into the dynamics of social commerce in Indonesia within the context of the local digital economy.